Building Student Engagement with Genially Interactive Media - Rahayu, Wening Patmi; Dede Rusmana; Cyndy Novi Octavia (Profesional Muda Cendekia Publishing, 2024)
Research Aims: This research was carried out based on the use of technology by teachers at SMK PGRI 2 Malang in implementing learning that was not yet optimal. This research aims to develop Genially interactive media so that it can increase student activity in classroom learning Design/methodology/approach: The method used in this research is Resources and Development using the ADDIE model. Product trials were carried out in class XI Digital Business. The data used in this research is qualitative and quantitative data. Data analysis was carried out using percentage analysis, normality test, and Independents Sample T-Test. This research produces Genially interactive media products that are attractive and served with various menus. Genially's interactive media has gone through the media and material expert validation stage Research Findings: The results of the analysis prove that there are differences in learning activity in the experimental class and the control class, so it can be concluded that this media is effectively used as a source of teaching materials and can increase students' learning activity Theoretical Contribution/Originality: The theoretical contribution of using Genially interactive media to build student engagement lies in its integration of multimedia elements with interactive learning, which enhances cognitive engagement and motivation. This approach aligns with constructivist theories of learning, emphasizing active participation and interaction with content. Genially’s originality stems from its ability to seamlessly combine various media—text, visuals, animations, and quizzes—into a single platform, offering a dynamic alternative to traditional learning tools. This innovation provides a novel way to create personalized, engaging learning experiences that can adapt to diverse educational settings.